PENGARUH NET PROFIT MARGIN, DEBT TO ASSET RATIO DAN CURRENT RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN SUB SEKTOR BATU BARA PERIODE 2018-2023 - Amelia Putri Tri Utami; Nurismalatri (Journal of Research and Publication Innovation, 2024)
This study aims to determine the influence of Net profit margin (NPM), Debt to asset ratio (DAR), and Current ratio (CR) partially and simultaneously on Stock Prices in coal sub-sector mining companies for the 2018-2023 period. This research is a quantitative research. The data collection technique used is a secondary source with documentation methods and literature studies. The data analysis technique used is panel data regression with a time series of 6 (six) years, namely the period 2018-2023 and with a cross section of 8 (eight) mining companies in the coal sub-sector. The results of the research conducted with a panel data regression test show that the best model used for this study is the Fixed Effect Model. Based on the results of the t-test, it shows that Net profit margin (X1) has a positive and significant effect on the stock price which is shown with a significant value of 0.0050 < 0.05. Meanwhile, the Debt to asset ratio (X2) and Current ratio (X3) have no significant effect on the stock price which is shown by a significant value in DAR of 0.9864 > 0.05, and a significant value in CR of 0.8572 > 0.05. Based on the results of the F Net profit margin test, Debt to asset ratio, and Current ratio together have a significant effect on the Stock Price with a significant value of 0.000000 < 0.05.